Menguatkan Nilai Integritas Melalui Sosialisasi Anti-Korupsi di Lingkungan Pendidikan - Zahra Amanda (Jurnal Akuntansi, Bisnis dan Ekonomi Indonesia (JABEI), 2025)
Corruption is one of the biggest challenges facing Indonesia,destroying publick trust and hindering national development. This aims to analyse the implementation of anti-corruption literacy outreach in school, including methods, challenges and impacts on students. This research uses a qualitative descriptive approach, whit data collected through interviews, observation and documentation in several primary and seconday schools. The results of the research show that thesocialization of anti-corruption literacy has been carried out throught the integration of anti-corruption values in the curriculum and campaigns. Despite facing obstacles such as limitide resources and lack of teacher training, thi program has had a positive impact on students’ understanding of the dangers of corruption, strengthening the values of honesty and integrirty.